Morphological and physicochemical characterization of biochar produced by gasification of selected forestry species (2017)
In this study, biochar samples acquired as by-product by downdraft gasification at 700 °C from Eucalyptus grandis (BC-EG), Acacia magnium (BC-AM) and Gmelina arborea (BC-GA) were characterized. The morphological characteristics and physicochemical properties of biochar were studied using nitrogen physisorption by the Brunauer-Emmet-Teller (BET) method, Scanning Electron Microscopy (SEM), X-ray Energy Dispersive Spectrometry (EDX) and Fourier Transform Infrared Spectroscopy (FTIR). The surface area (SA) of the materials was in the 2.0-50.0 m2/g range, with the biochar obtained from BC-EG showing the highest SA (50.0 m2/g), while the biochar derived from BC-GA showed the lowest SA (2.0 m2/g). In addition, all samples can be classified as mesoporous materials because their pore sizes were between 2 and 50 nm. This indicates that these materials can be used in absorption processes; however, the biochar obtained from BC-AM is expected to be the most suitable for absorption applications. FTIR biochar spectra did not exhibit characteristic peaks for cellulose or hemicellulose in any sample due to decomposition of these compounds at the gasification temperature. Moreover, according to SEM/EDX analyzes, all the samples presented well-defined pore structure and contained minerals as Na, K and Ca, suggesting that the biochar could also be useful for soil amendment applications.